Online Forums as a Mirror Reflecting the World of ESP - Agnieszka Dzięcioł-Pędich (National Research University Higher School of Economics, 2016)
The article presents the analysis of most frequent threads in four Internet forums to see what can be learnt about ESP teachers' interests and understanding of the concept of English for Specific Purposes (ESP). The results show that the majority of discussions revolve around the choice of materials for different types of ESP. This might suggest that forum members know very little about oral and written communicative strategies of a given profession and rely on the expertise of course books writers to provide them with such knowledge. Moreover, the analysis shows that forum members do not discuss how to teach individual language skills but how to teach different types of ESP which might indicate that there is a greater difference between teaching the same skills in two branches of ESP than there is between teaching different skills with a single type of ESP. The results also indicate that some users feel that ESP teachers should be interested in more than just linguistics, but there are those who claim that the main difference between ESP and general English lies in vocabulary. This polarity of opinions shows that no established view of ESP may exist. The analysis further suggests that the distinction between ESP and EGP is clearer to those who are more interested in learners' professional needs. Finally, the choice of topics in the analysed threads indicates that forum members and their visitors are interested not only in ESP, but in subjects which have nothing to do with ESP.